Negotiating experience in patient involvement: Challenges of practicing storytelling in health care conversations - Terkelsen, Morten Deleuran; Wittrup, Inge (Tidsskrift for Forskning i Sygdom og Samfund, 2015)
This paper investigates the challenges of integrating patient experiences in patient involving health care interventions. Experience occupying a central importance is often perceived to be something inherent to the patient to be communicated to the health professional during conversations. Yet drawing on empirical material from an ‘Intercultural Health Conversation’ and by departing in anthropological debates seeing experience as something socially expressed and negotiated this article demonstrates how boundaries and constraints emerge when experiences become socially expressed through the practice of storytelling in conversations in health care.